2003
DOI: 10.1038/sj.leu.2403062
|View full text |Cite
|
Sign up to set email alerts
|

Serial minimal residual disease (MRD) analysis as a predictor of response duration in Philadelphia-positive acute lymphoblastic leukemia (Ph+ALL) during imatinib treatment

Abstract: Patients with refractory or relapsed Philadelphia chromosomepositive acute lymphoblastic leukemia (Ph+ALL) rarely have prolonged responses to salvage therapy, including imatinib, resulting in a short opportunity for potentially curative stem cell transplantation. To identify minimal residual disease (MRD) parameters predictive of imminent relapse, we quantitated BcrAbl expression by real-time PCR in peripheral blood (PB) and bone marrow (BM) of 24 Ph+ALL patients after achieving a complete response and MRD min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…1). Although the previous report suggested that BM samples were shown to be the more discriminatory and reliable materials as compared to PB in case of Ph+ ALL (Scheuring et al 2003), we speculate that more frequent sampling of PB may increase the ability to detect significant increase of MRD. Since early relapse is common and predicts a poor outcome in Ph+ ALL, MRD quantification at a very early stage of SCT should be important for the stratification of high risk patients who need further treatment intervention.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…1). Although the previous report suggested that BM samples were shown to be the more discriminatory and reliable materials as compared to PB in case of Ph+ ALL (Scheuring et al 2003), we speculate that more frequent sampling of PB may increase the ability to detect significant increase of MRD. Since early relapse is common and predicts a poor outcome in Ph+ ALL, MRD quantification at a very early stage of SCT should be important for the stratification of high risk patients who need further treatment intervention.…”
Section: Discussionmentioning
confidence: 76%
“…Several approaches to treat relapsed leukemia after SCT, including donor lymphocyte infusion, second SCT and chemotherapy, do not benefit significant proportion of patients because of toxicity associated with the procedure or disease progression. Therefore, imatinib, which is well tolerated and has a manageable side-effect profile (Kantarjian et al 2002;Olavarria et al 2002Olavarria et al , 2003Ottmann et al 2002;Wassmann et al 2002;Scheuring et al 2003;Shimoni et al 2003), might be a useful strategy to be used in conjunction with SCT. However, the clinical role of imatinib in Ph+ leukemia in the setting of SCT remains to be defined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In future trials, it has to be prospectively assessed whether MRD analysis in peripheral blood which is more convenient and costeffective mirrors changes in bone marrow samples, as has been shown for MRD assessment in other leukemia entities. [40][41][42] Although based on a few patients due to incomplete accrual, a significant trend towards longer PFS for alemtuzumab-treated patients was seen at a median follow-up of almost 2 years. We are fully aware that these results have to be taken cautiously and that this trend needs to be confirmed after a longer follow-up, especially in light of residual splenomegaly and/or lymphadenopathy in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…29 With the addition of targeted treatment such as imatinib mesylate to current chemotherapy regimens for BCR-ABL þ ALL, BCR-ABL transcripts have become the first-choice marker for MRD monitoring by RT-RQ-PCR. 30,31 In contrast, TEL-AML1 fusion gene occurring in approximately 25% of children with ALL identifies a subgroup with a very good prognosis for which the advantage of MRD monitoring is not yet fully proven.…”
Section: Rq-pcr-based Quantification Of Leukemia-associated Fusion Genesmentioning
confidence: 99%